Paradox of the best in Fronting & Postponement - Salah, Wasan (Al-Adab Journal, 2020)
Heritage has inadvertently exercised a control role in rhetorical issues, it kept a problem is each topic to be argued and discussed, which ensured its durability and its appeal , and of those issues (care of the fronting because it is the most important) that are present in the topic (fronting and postponement), This issue left a successful effect for the strength of its pillars to be a gateway to other issues within a conceptual framework of objective facts and psychological demands fueled by reality, but the following-up of the Quranic and other poetic texts came to my mind changed against it by giving importance to the postponement, relying on matters of knowledge and living facts.The facts lined up to justify the use of this way, especially in the locations of steadily postponement and the having the postponed as the comment in the beginning of ayas or sentences or poetry rhyme, which makes attention to be growing.